Perluasan Pasar dan Penambahan Umur Simpan Ikan Asap Desa Gebang, Bangkalan, Madura dengan Teknologi Pengemasan Vakum - Supandi Hermawan; Roelly Ainul Yaqin; Abdul Adhim; Eviyanti Choirunnisa; Rizqiyatul Amaliyah; I Wayan Astika (Jurnal Pusat Inovasi Masyarakat (PIM), 2021)
Most of the people of Gupot Tanjung, Gebang Village make their living as smoked fish entrepreneurs. Smoked fish processing activities has become the identity of the people of Gupot Tanjung, but the smoked fish processing is still carried out conventionally and is sold openly in the local market, so it is necessary to develop innovations to increase the added value of the product. The innovative use of vacuum packaging and online marketing can be applied to smoked fish products. The existence of this innovation can minimize smoked fish products from various kinds of residues and diseases and expand market reach. This activity aims to improve knowledge and skills related to the shelf-life of smoked fish products, vacuum plastic wrapping methods, and expansion of product marketing reach. The implementation method consists of several activities, namely the socialization of product innovation, the practice of vacuum packaging and labeling, online marketing, and discussions. The results showed that the vacuum packaging innovation provided added value to the product by increasing the shelf life of fish from 2-3 days to 4-7 days. Online marketing is carried out through social media Facebook, WhatsApp and Instagram to expand the product market reach. Apart from being carried out online, marketing is also carried out directly at Car Free Day activities. Keywords: smoked fish, packaging, marketing